Darcy-Forchheimer Flow of MHD Powell-Eyring Nanoliquid over a Nonlinear Radially Stretching Disk with the Impact of Activation Energy - Macha, Madhu; Prabhakar, Besthapu (Discontinuity, Nonlinearity, and Complexity, 2026)
This study proclaims the Darcy-Forchheimer flow of Powell- Eyring nanoliquid subjected to nonlinear radially stretching disk. Further the impact of activation energy retained in concentration expression. In addition to this, convective boundary condition is adopted together with a modified version of mass flux condition is used. The modeled partial differential equations have been remodeled into system of ordinary differential equations via appropriate similarity variables. These ODEs are solved by Runge-Kutta fourth order scheme along with shooting technique. Graphs have been prepared to analyze the features of various influential parameters on velocity, temperature and concentration fields. Significant effects are found for various estimations of the fluid parameter on velocity, temperature and concentration profiles. Velocity field is reduced for growing values of porosity as well as inertia coefficient. Concentration rises for larger values of energy parameter but it is depreciated for higher values of chemical reaction rate.